UPAYA MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS (TGT) PADA SISWA KELAS VII B SMP N 2 PAKEM - Asri Nur Yulianti; A. A Sujadi (Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of this research was to know the learning process and mathematics achievement students of class VII B SMP N 2 Pakem with cooperative learning type Teams Games Tournamennts (TGT) model. This research is Classroom Action Research. The subjects in this research were students of class VII B which is 32 students. The data collecting technique in this research was done by using observation, documentation and tests. The result of this research showed an increase in the learning process and achievement of students in the learning process. This is indicated by an increase in percentage of students learning process on the first cycle is 59,82%, while on the second cycle increased to 68,75%. The percentage of the KKM students of class VII B also increased, pre-cycle at 15,625% increased to 59,35% in the first cycle, the second cycle again increased to 65,625%.